Ecology and management of black walnut (Juglans nigra L.) in Hungary - Rédei, Károly (Array, 2019)
Background and Purpose: Black walnut (Juglans nigra L.) was one of the first forest tree species introduced and acclimated from North America to Europe in the 17th century. Although native to North America, black walnut is now naturalized and widely planted throughout Europe. In Hungary, this species has played an important role in forest management. Black walnut can grow on various sites, but careful site selection and well-planned management practices are needed to produce successful plantations. Due to the increasing interest in black walnut growing in many countries this study complied with the aim of giving a summary on the base of research and improvement connected with the species over the past decades. Materials and Methods: Black walnut produces a well-closing, favourably differentiated stand structure in consequence of the great genetic diversity of single trees. It utilizes well the leaks of the tending cuttings. In this manner, because of its quick height growth, the systematic, individual selective method can be favourably combined with more frequent stem number reduction. The objective of tending should be to produce a high proportion of good quality saw logs from stands of yield class I, II, III and IV, and some other smaller-dimension industrial wood from stands of yield class V and VI. Conclusions: In Hungary, black walnut is one of the most valuable exotic tree species, mainly because of its wood excessively used in furniture industry. Black walnut is used in furniture industry both as solid wood and veneer. This species is among the most expensive furniture woods in the world due to its appealing surface figure and colour. Its wood is also used for making musical instruments, turned and carved ornaments, statues and marquetry. Black walnut stands are to be important in carbon sequestration, soil stabilization, and water quality protection as well.